Literature Review: Kepuasan Pasien Rawat Jalan di Puskesmas pada Masa Pandemi Covid-19 - Ika Rodhifatun Nadhifah; Diansanto Prayoga (Media Gizi Kesmas, 2023)
Background: Satisfaction with various services is determined by the extent to which service providers provide the best for their consumers, including health service providers at the puskesmas. Puskesmas as a first-level health facility should provide satisfactory services for visitors. Satisfactory service can lead to loyalty to visitors, thereby reducing the use of illegal health services that can endanger health. During this Covid-19 pandemic, various puskesmas services have differed in several procedures due to adjustments to the Covid-19 pandemic policy. This difference in service procedures is thought to have an effect on patient satisfaction. Objectives: This journal has the aim of knowing the outpatient satisfaction at the health Center during the Covid-19 pandemic. Methods: The procedure for this research uses a literature review approach using the PRISMA flowchart. Collection of references through several online databases, namely Google Schoolar, ScienceDirect, Proquest, Wiley Online, Sage Publication and Media Neliti. The keywords used in the search were Satisfaction, Outpatient Patients, Puskesmas and Covid-19 Pandemic. Results: The results showed that the results varied with positive and negative responses regarding the loyalty of outpatients during the Covid-19 pandemic which was influenced by considerations of the suitability of the perception of the application of technical control, the perception of the application of administrative control, the perception of the application of PPE (Personal Protective Equipment). Another thing is information about the availability of infrastructure facilities, attitudes of health workers, knowledge and referrals with patient perceptions that affect age and education level. Conclusions: Outpatient satisfaction at the puskesmas during the Covid-19 pandemic was relatively good, but there were several influencing factors including the application of personal protective equipment (PPE), administrative control, technical control, information on the availability of infrastructure, attitudes of health workers, knowledge and referrals with the patient's perception that affects age and education level.